Характеристики перенапруженого наносекундного розряду між електродами з халькопіриту (CuInSe2) в безкисневих газових середовищах - Shuaibov, A. K.; Minya, A. I.; Malinina, A. A.; Gritsak, R. V.; Malinin, A. N. (Publishing house "Academperiodika", 2020)
The characteristics of the nanosecond overvoltage discharge ignited between semiconductor electrodes based on the CuInSe2 chalcopyrite compound in the argon and nitrogen atmospheres at gas pressures of 5.3–101 kPa are reported. Due to the electrode sputtering, chalcopyrite vapor enters the discharge plasma, so that some CuInSe2 molecules become destroyed, whereas the others become partially deposited in the form of thin films on solid dielectric substrates located near the plasma electrode system. The main products of the chalcopyrite molecule decomposition in the nanosecond overvoltage discharge are determined; these are atoms and singly charged ions of copper and indium in the excited and ionized states. Spectral lines emitted by copper and indium atoms and ions are proposed, which can be used to control the deposition of thin chalcopyrite films in the real-time mode. By numerically solving the Boltzmann kinetic equation for the electron energy distribution function, the electron temperature and density in the discharge, the specific losses of a discharge power for the main electronic processes, and the rate constants of electronic processes, as well as their dependences on the parameter E/N, are calculated for the plasma of vapor-gas mixtures on the basis of nitrogen and chalcopyrite. Thin chalcopyrite films that effectively absorb light in a wide spectral interval (200–800 nm) are synthesized on quartz substrates, by using the gas-discharge method, which opens new prospects for their application in photovoltaic devices.